Evaluating the impact of uncontrolled traffic sources upon real-time communication in IEEE 802.11s mesh networks - Carlos M. D. Viegas (2014)
This paper assesses the interference caused by uncontrolled traffic sources upon real-time traffic in IEEE 802.11s mesh networks. It was considered a mesh network transmitting real-time traffic and an external interference was injected in order to evaluate its impact over the real-time communication. A set of experiments were performed in ns-3 and different scenarios were evaluated, where the end-to-end delay, message loss and deadline miss ratios were chosen as performance metrics. It can be inferred that the real-time traffic in 802.11s is highly affected by external interferences, and therefore that must be taken into account when setting-up such type of networks.